Analysis of the Effect of Foreign Workers on Unemployment in Banten Province - Muchlis, Aditia; Fiqhi, Afif; Mumtazah, Liza (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
The purpose of this research is to analyze issues related to unemployment influenced by foreign workers in Banten Province. The specific objective is to deepen the study related to strategic efforts to increase government capacity to improve the quality of human resources in overcoming unemployment in Banten Province. This research uses a qualitative method based on a combination of primary and secondary data processing conducted using a discourse analysis approach. Data collection methods used in this research are interviews and documentation, in addition to discussions related to strengthening field data. Based on the discussion that has been explained above, the researcher draws the conclusion that foreign workers do not have a significant impact on unemployment in Banten Province; knowlage transfer is needed and becomes a priority scale rather than profit sharing; work ethic is an important asset that must be owned by job seekers and those who are already working.